Propionibacterium acnes is the most common bacterium commensal in peripheral lung tissue and mediastinal lymph nodes from subjects without sarcoidosis - Ishige, Ikuo; Eishi, Yoshinobu; Takemura, Tamiko; Kobayashi, Intetsu; Nakata, Koh; Tanaka, Isao; Nagaoka, Sakae; Iwai, Kazuro; Watanabe, Kunitomo; Takizawa, Touichiro; Koike, Morio (Sarcoidosis, vasculitis, and diffuse lung diseases, 2005)
In studies of the unknown etiology of sarcoidosis, Propionibacterium acnes (a possible agent) was found in the lungs and lymph nodes of many sarcoidosis patients and some control subjects. P. acnes might be commensal not only to the skin, conjunctivae, and intestine, but also to the lungs and lymph nodes of individuals without sarcoidosis. We cultured peripheral lung tissue and various lymph nodes obtained from patients with diseases other than sarcoidosis. DNA of 45 isolates of P. acnes from these patients, 67 isolates from normal skin, conjunctiva, and intestine, and 39 isolates from sarcoid lymph nodes were compared by random amplified polymorphic DNA analysis. P. acnes was isolated from half of 43 lungs and 8 of 11 mediastinal lymph nodes, mostly in pure culture. P. acnes was isolated from half of 20 gastric and 3 of 12 intestinal lymph nodes; intestinal bacteria were also numerous. In general, fewer than 500 colony-forming units of P. acnes per gram tissue were isolated, but 4 lung tissue specimens, 2 of which had a few granulomas, had many more. P. acnes strains from a particular site (lung, lymph node, skin or conjunctivae, and intestine) were genetically similar, more than isolates obtained from different sites. Lymph-node isolates from subjects with and without sarcoidosis differed little. These results suggest that P. acnes normally resides in peripheral lung tissue and mediastinal lymph nodes and that the strains of P. acnes isolated from sarcoid lymph nodes were not specific to sarcoidosis.